Selection of production lines in the metallurgical industry using the Compromise Programming method - Radivojević, Srbislav; Maksimović, Mlađan; Karabašević, Darjan; Novaković, Srđan (Mining and Metallurgy Engineering Bor, 2018)
Every organization today faces the problem of decision making. In this regard, the intent of this paper is to present an approach based on the multi-criteria decision-making methods. Primarily, the proposed approach is aimed to help solving problem of choosing the optimal production lines in the metallurgical industry. The proposed approach is based on the use of the AHP method for determining the weights of criteria, whereas the Compromise Programming is used for selection the alternatives. The usability, applicability and efficiency of the proposed approach is demonstrated in a conducted case study of selection the production lines in the metallurgical industry.